Physiotherapy education and game-based learning: developing the SPINE framework - Diana Filipa Salvador Bernardo; Manuel Joaquim da Silva P. G. Paquete; Marlene Cristina Neves Rosa (Institute of Advanced Engineering and Science, 2026)
Innovative pedagogical approaches are increasingly essential in physiotherapy education to foster engagement and competency development. This multicenter cross-sectional study explored physiotherapy students’ perceptions of game-based learning (GBL) across six Portuguese higher education institutions. A total of 208 students completed a structured questionnaire assessing attitudes toward GBL in teaching–learning contexts and competency development. Results indicated generally positive perceptions of GBL, emphasizing its value for motivation, engagement, and integration of theoretical and practical learning. Transversal competencies—such as teamwork, communication, and empathy—were consistently recognized across academic years, while perceived benefits for technical skills increased with clinical exposure. Female students and those with prior health-related experience reported more favorable attitudes. However, students also highlighted limited curricular implementation and the need for clearer alignment between game activities and learning objectives, suggesting barriers at the institutional and pedagogical levels. These insights point to a gap between students’ enthusiasm and current educational practices, underlining the importance of structured guidance for integrating GBL effectively. Building on these findings, the student-perceived integration for novel education (SPINE) framework is proposed as a decision-making model to guide the pedagogically grounded GBL in physiotherapy curricula, emphasizing evidence-informed, context-sensitive, and sustainable implementation.